Physicochemical Properties of Lamotrigine and its Compatibility with Various Inactive Ingredients to Formulate Lamotrigine Orally Disintegrating Tablets - Gangavarapu, Pavan Kumar (International Journal of Pharmaceutical & Biological Archive, 2013)
Physicochemical Properties of Lamotrigine and its Compatibility with Various Inactive Ingredients to Formulate Lamotrigine Orally Disintegrating Tablets